High-performance W–Cu composites preparation technology, modulation strategy and strengthening mechanism - Weiyang Long; Yifan Yan; Mingzhu You; Haoran Wu; Zheng Wei; Hongfei Zhang; Shaodan Yang; Zhiyuan Zhu; Kexing Song (Journal of Materials Research and Technology)
W–Cu composites are widely used as electrode materials, electronic packaging materials, heat sinks, and targets in the defense industry, aerospace, and electronic information fields due to their good conductivity, high melting point, good mechanical properties, and good anti-arc erosion performance. In recent years, high-performance W alloys have gradually become the key materials in the defense industry and cutting-edge technologies, and new processing technologies have greatly improved the material density, uniformity of microstructure, mechanical properties, and physical properties of W alloys, but have also raised higher requirements for the high reliability, zero accidents, and long service life of defense and military materials. By optimizing the composite design and fabrication process, controlling the growth of microstructure and interfacial diffusion, and improving the fine grain distribution and uniformity, the densification, mechanical properties, and anti-arc erosion performance of W–Cu composites can be further improved. This paper reviews the evolution of preparation technology and modulation strategy for W–Cu composite, discusses the relationship between microstructure growth and mechanical properties of W–Cu composites, and systematically summarizes the influence mechanisms of alloy element content, existence form and microstructure on the electrical and thermal conductivity, strength, and erosion resistance of W–Cu composites. Finally, the future development trends and application prospects of W–Cu composites, including ultra-high voltage switchgear, hypersonic thermal protection systems and electromagnetic rail gun components, are prospected. The research results can provide reference for the material component design, advanced fabrication technology, microstructure and performance control of high-performance W–Cu composite materials in key fields and extreme service evaluation.